Does tuberculosis threaten our ageing populations? - Byng-Maddick, Rachel (BMC Infect Dis, 2016)
BACKGROUND: The global population is ageing quickly and our understanding of age-related changes in the immune system suggest that the elderly will have less immunological protection from active tuberculosis (TB). DISCUSSION: Ongoing global surveillance of TB notifications shows increasing age of patients with active TB. This effect of age is compounded by changes to clinical manifestations of disease, confounding of diagnostic tests and increased rates of adverse reactions to antimicrobial treatment of TB. Future epidemiological surveillance, development of diagnostic tests and trials of treatment shortening should all include a focus on ageing people. SUMMARY: More detailed surveillance of TB notifications in elderly people should be undertaken and carefully evaluated. Risk stratification will help target care for those in greatest need, particularly those with comorbidities or on immunosuppressive therapies. Novel diagnostics and treatment regimes should be designed specifically to be used in this cohort.